2023
DOI: 10.3389/fimmu.2023.1187332
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glycoproteomic biomarkers identify metastatic melanoma patients with reduced clinical benefit from immune checkpoint inhibitor therapy

Abstract: The clinical success of immune-checkpoint inhibitors (ICI) in both resected and metastatic melanoma has confirmed the validity of therapeutic strategies that boost the immune system to counteract cancer. However, half of patients with metastatic disease treated with even the most aggressive regimen do not derive durable clinical benefit. Thus, there is a critical need for predictive biomarkers that can identify individuals who are unlikely to benefit with high accuracy so that these patients may be spared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Although currently underexplored, glycoprofiling of new or validated drug targets represents a valuable opportunity for the development of next-generation therapeutics that may achieve exquisite selectivity by binding to distinct glycosylation variants. In addition, the recent discovery of fucosylated biomarkers in the blood of melanoma patients that failed to achieve extended survival after treatment with immune checkpoint inhibitors points to a role of glycosylation not only in the tumor but also in the periphery (26,27). Therefore, glycosylation analysis of circulating glycoproteins may offer crucial information for both drug design and biomarker discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although currently underexplored, glycoprofiling of new or validated drug targets represents a valuable opportunity for the development of next-generation therapeutics that may achieve exquisite selectivity by binding to distinct glycosylation variants. In addition, the recent discovery of fucosylated biomarkers in the blood of melanoma patients that failed to achieve extended survival after treatment with immune checkpoint inhibitors points to a role of glycosylation not only in the tumor but also in the periphery (26,27). Therefore, glycosylation analysis of circulating glycoproteins may offer crucial information for both drug design and biomarker discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that camrelizumab and cemiplimab specifically interact with a fucose moiety within the N58 glycan of PD-1. As fucosylation is increased in cancer and fucosylated biomarkers in blood have been associated with a lack of benefit of immune checkpoint inhibitor therapy (26,27), we investigated the influence of fucosylation on PD-1 in antibody activity by a combination of protein-and cell-based assays. Furthermore, we characterized fucosylation of sPD-1 in the serum of individuals with non-smallcell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation is a common post-translational modification of proteins, and it impacts their polarity, solubility, structure, cellular localization, and interactions with other molecules. , Thus, it is unsurprising that changes in glycosylation coincide with many diseases and aberrant glycosylation is implicated in cancer development and progression. In addition, glycoproteins have a long-standing recognition as cancer biomarkers. Poly- N -acetyllactosamine (polyLacNAc) is a linear carbohydrate polymer composed of alternating N -acetylglucosamine and galactose residues that is found mainly on tri- and tetra-antennary N -glycans and preferentially on the branch initiated by the β1–6 N -acetylglucosaminyltransferase-V encoded by the Mgat5 gene. , PolyLacNAc contributes to cancer resistance against T cell killing and increases the stability of the PD-L1 protein at the cell surface, leading to an enhanced interaction with the PD-1 receptor and reduced cytotoxic T cell responses in cancer . PolyLacNAc may also exhibit context-dependent roles in cancer cells: the presence of sialyl Lewis X on polyLacNAc-elongated glycans may lead to metastasis, while the same epitope on truncated N -glycans results in the death of tumor cells in lung blood vessels .…”
Section: Introductionmentioning
confidence: 99%
“… 3 6 In addition, glycoproteins have a long-standing recognition as cancer biomarkers. 7 9 Poly- N -acetyllactosamine (polyLacNAc) is a linear carbohydrate polymer composed of alternating N -acetylglucosamine and galactose residues that is found mainly on tri- and tetra-antennary N -glycans and preferentially on the branch initiated by the β1–6 N -acetylglucosaminyltransferase-V encoded by the Mgat5 gene. 10 , 11 PolyLacNAc contributes to cancer resistance against T cell killing 12 and increases the stability of the PD-L1 protein at the cell surface, leading to an enhanced interaction with the PD-1 receptor and reduced cytotoxic T cell responses in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms by which GALC exerts its pro-tumorigenic functions in human melanoma remain poorly understood. Analysis of the proteome may provide valuable information for the characterization of the biological pathways leading to melanoma progression [12][13][14][15][16] and for the identification of diagnostic and prognostic biomarkers [17][18][19][20]. As stated above, GALC may exert a pro-oncogenic role in Braf wild-type murine melanoma cells [5].…”
Section: Introductionmentioning
confidence: 99%